Inventory of ambivalent sexism: a study from the structural equation modeling - Formiga, Nilton S. (2015)
The aim of this study is evaluate, from the structural equation modeling, the inventory of ambivalent sexism. This instrument, adapted by Formiga, Gouveia, and Santos (2002) is made of 22 items, answered in a scale of five points. Two factors are assessed: hostile sexism and benevolent sexism. 620 people, men and women, between 16 and 47 years old, from the city of Palmas-TO and João Pessoa-PB composed the study. The inventory was applied individually, in schools and streets of both cities ensuring the anonymity and confidentiality of responses. From the program AMOS GRAFICS 7.0 the indicators of goodness, of fit accepted in current literature confirmed the existence of the two factors, according to the Brazilian studies found about the theme.